Tariff Revenue and Tariff Caps - Amador, Manuel; Bagwell, Kyle (American Economic Review, 2012)
We characterize the design of an optimal trade agreement when governments are privately informed about the value of tariff revenue. We show that the problem of designing an optimal trade agreement in this setting can be represented as an optimal delegation problem when a money burning instrument is available. In a specification with quadratic payoffs and a uniform distribution, we find that the tariff cap and the probability of binding overhang are higher when the upper bound of the support distribution is higher and when the support distribution has greater width.